Spring Water Quality in a Flood-Prone Area of Kampala City, Uganda: Insights Furnished by Sanitary and Limnochemical Data - Tenywa, Ronald; Omara, Timothy; Kwikiriza, Gerald; Angiro, Christopher; Ntambi, Emmanuel (Resources, 2024)
For millennia, springs have provided water for drinking, domestic use, balneological treatment, liminality rites as well as tourist attractions. Amidst these uses, anthropogenic activities, especially urbanization and agriculture, continue to impair the functionality of springs. With the looming decadal climate change, freshwater springs could be a sustainable source of clean water for the realisation of Sustainable Development Goal 6. This paper presents the results of the sanitary inspection and assessment of limnochemical characteristics and quality of water samples (n=64) from four freshwater springs (coded SPR1, SPR2, SPR3, and SPR4) in Kansanga, a flash flood-prone area in the African Great Lakes region of Uganda. Each sample was analysed for 17 parameters (temperature, pH, electrical conductivity, turbidity, fluorides, sulphates, chlorides, nitrates, orthophosphates, total dissolved solids, dissolved oxygen,total alkalinity, potassium, sodium, total, magnesium and calcium hardness) following the standard methods. Water quality index (WQI) was calculated to establish the quality of the water samples based on the physicochemical parameters measured. Based on the sanitary risk assessment results, the springs had medium- to high-risk scores, but most water parameters were within the WHO guidelines for potable water, except for nitrates (in SPR1 and SPR2), hardness levels (in SPR2), and dissolved oxygen (in all the samples). Sampling season and location had significant effects on the limnochemistry of the freshwater springs (p < 0.05). The water quality indices calculated indicated that the water from the springs was of good quality (WQI = 50–57), but there was a reduction in water quality during the wet season. The best water quality was recorded in samples from SPR4, followed by those for SPR3, SPR1, and SPR2. These results provide insights into the contribution of floods and poor sanitation facilities to the deterioration of spring water quality in Kansanga, and the need to leverage additional conservation strategies to support vulnerable communities in the area. Further studies are required to establish the risk posed by trace metals and microbes that may contaminate freshwater in the studied springs, especially following flood events.
Keywords: Potable water; Physico-chemical quality; Water quality index